The Antibacterial Effectiveness of Red Ginger (Zingiber Officinale Roscoe) Essential Oil in Inhibiting The Growth of Staphylococcus Aureus and Streptococcus Mutans - Shavilla Lukita; Winda Khosasi; Chandra Susanto; Florenly (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Red ginger extract has a category strong antibacterial effect on Staphylococcus aureus and Streptococcus mutans. Red ginger essential oil has the potential for stronger inhibition. This study aims to compare the antibacterial effectiveness of red ginger essential oil against Staphylococcus aureus and Streptococcus mutans. The design of this study was a laboratory experimental design with a factorial completely randomized design. The red ginger used in this study was proven to be a species of Zingiber officinale Roscoe. The production of essential oils in this study uses the steam distillation method. The content of secondary metabolites in red ginger was tested quantitatively by the GC-MS method. Determination of antibacterial activity using the disc diffusion method. The data were processed using the SPSS 21.0 program. The normality of data distribution was tested with the Shapiro-Wilk test, followed by one-way ANOVA, Levene's test, and the Tukey HSD Post Hoc Test. The results of the antibacterial test of red ginger essential oil against Staphylococcus aureus (21.21mm ± 0.315) and Streptoococcus mutans (23.43mm ± 0.189) prove d that the inhibition power of the category was very strong at a concentration of 75%.